Teaching behaviours of clinical teachers and professional commitment among nursing students: A moderated mediation model of optimism and psychological well-being. (June 2023) - Zhao, Fang-Fang
Abstract: Background: Understanding the paths that influence professional commitment among nursing students is important for helping students continue the nursing profession after graduation. The paths between the teaching behaviours of clinical teachers (TBCT) and professional commitment were unknown. Objectives: This study aimed to examine whether psychological well-being mediated the relationships between the teaching behaviours of clinical teachers and professional commitment of nursing students. Moreover, we investigated whether the mediating effects of psychological well-being were moderated by optimism. Design: A cross-sectional design was conducted. Setting and participants: A total of 318 students from 24 hospitals in 13 cities in northern, north-eastern, and eastern China were included in the study. Methods: The instruments used in this study included the scale of teaching behaviours of clinical teachers, a brief inventory of thriving (measuring psychological well-being), a life orientation test (measuring optimism), and a professional commitment scale. The PROCESS macro for SPSS was used to perform mediation analysis and moderated mediation analyses. Results: Psychological well-being of nursing students partially mediated the relationships between the teaching behaviours of clinical teachers and professional commitment of nursing students. Also, optimism moderated the indirect effect of this mediation model. The indirect effect of clinical teachers' teaching behaviours was stronger for nursing students with low levels of optimism. Conclusion: The findings suggest that the teaching behaviours of clinical teachers and psychological well-being promote professional commitment. In addition, the mediation of psychological well-being between the teaching behaviours of clinical teachers and professional commitment was conditional on different levels of optimism. Clinical teachers should pay special attention to students with low levels of optimism because teaching behaviours of clinical teachers exert more influence on those students' professional commitment. Highlights: Psychological well-being mediates the relation between teaching behaviours of clinical teachers and professional commitment. The teaching behaviours of clinical teachers are more strongly related to psychological well-being among students with low optimism. Teaching behaviours exert more influence on professional commitment of students who have low levels of optimism.